A New Standard Gerbera Cultivar Harmony with Pink and Semi-double Adaptable to High Temperature - Park, S.K., National Institute of Horticultural and Herbal Science, suwon, Republic of Korea; Lim, J.H., Sejong University, Seoul, Republic of korea; Choi, S.Y., National Institute of Horticultural and Herbal Science, suwon, Republic of Korea; Shin, H.K., National Institute of Horticultural and Herbal Science, suwon, Republic of Korea; Huh, E.J., National Institute of Horticultural and Herbal Science, suwon, Republic of Korea (Weon'ye gwahag gi'sulji, 2013)
A new gerbera cultivar Harmony’ was bred by the National Institute of Horticultural and Herbal Science in 2010. Pavilov with pink and Marathon with purple, which have semi-double flower, were crossed in 2007. After investigation of the characteristics for four years (from 2007 to 2010), it was selected specially for the use as a cut flower. The Harmony had brilliant pink color (RHS R49B) with dark brown center. The flower was semi-doubled with 11.8 ㎝ in diameter. It had a long and thick peduncle with length and upper width 59.2 ㎝ and 3.9 ㎜, respectively. The vase life of Harmony was 12.0 days, which was 3 days longer than the control cultivar. And its average yield was 57.0 stems per plant, which were 10.5 stems more than the control.